Mucosal Mast Cells Contribution in Intestinal Defense of Chickens (Gallus domesticus) Infected Naturally by Ascaridia galli - Ummu Balqis; Masda Admi; Darmawi Darmawi; Muhammad Hambal (Syiah Kuala University, 2015)
This study was aimed at finding out the investigation of mucosal mast cells in intestines of chicken that were naturally infected by Ascaridia galli. Amount of ten intestine of freshly slaughtered chickens (Gallus domesticus) found from local abatoir in Banda Aceh were divided into two groups containing five intestines of each. Mucosal mast cells count were done of which histologic slides were made in stained serial histological sections with Alcian blue (pH 0,3) and Safranin-O (pH 0,1) of the intestines. The result showed that the mucosal mast cells increased significantly (P 0.05) in intestines of chickens infected naturally by survival A. galli adult worms. It was concluded that the intestinal defense of chickens against parasite infection is associated with the mucosal mast cells contribution by creating an environment hostile to the establishment and survival of intestinal nematodes, A. galli.